The response of the rabbit rectococcygeus muscle to stimulation of extrinsic inhibitory nerves and to sympathomimetic drugs - King, B.F. (1981)
1 The effects of stimulating sympathetic or non-adrenergic non-cholinergic (NANC) nerves or of the addition of noradrenaline (NA) or isoprenaline (Iso) were investigated on carbachol-induced tone and on contractions produced by acetylcholine (ACh) and by pelvic nerve stimulation, in the rabbit rectococcygeus muscle. 2 Each procedure reduced carbachol-induced tone; sympathetic and NANC nerve stimulation were equipotent but both were less effective than sympathomimetic drugs, of which Iso was the better. Both Iso and NA, but not sympathetic nerve stimulation, inhibited the contractions produced by pelvic nerve stimulation in a concentration-dependent manner. Against ACh-induced contractions, only Iso was effective. The effects of NANC nerve stimulation on the motor responses to pelvic nerve stimulation or to ACh were not investigated. 3 The inhibitory effects of sympathetic nerve stimulation, of Iso and of NA were reduced by propranolol (3 × 10(-6) M) but unaffected by phentolamine (3 × 10(-5) M). 4 In the presence of high (45 mM) concentrations of KCl, Iso and NA produced a concentration-dependent inhibition of tone that was antagonized by propranolol (3 × 10(-6) M). 5 Methoxamine (4 × 10(-7) to 4 × 10(-5) M) and phenylephrine (5 × 10(-7) to 5 × 10(-5) M) which interact mainly with α(1)-adrenoceptors, produced only small, transient reductions in carbachol-induced tone which were subject to tachyphylaxis, unlike those produced by Iso and NA. These inhibitory effects were antagonized by phentolamine (3 × 10(-6) M) or azapetine (3 × 10(-6) M). 6 Phenylephrine (5 × 10(-4) M) and high doses (3 × 10(-5) M or greater) of NA enhanced the contractile response to pelvic nerve stimulation and, on occasion, produced muscle contraction. These effects were antagonized by phentolamine (3 × 10(-6) M). 7 These results suggest that inhibition of the rectococcygeus, a muscle which has no intramural nerve plexus, can be inhibited by stimulation of extrinsic NANC nerves, the transmitter for which is unknown and by sympathetic nerve stimulation via α- and β-adrenoceptors located postsynaptically on the muscle. Excitatory α-adrenoceptors may also be present.